Implementasi PP No 61 Tahun 2010 di Pemerintahan Kota Pematangsiantar - TRIMURNI, FEBRUATI; BAKARA, SRI DEWI SARTIKA (Politeia: Jurnal Ilmu Politik, 2012)
The government of Pematangsiantar Municipality is one local government that has interpreted the regulations of Government Regulation (Peraturan Pemerintah/PP) Number 61/2010 and has started to implemented its regulation by issuing Municipal Regulation (Peraturan Walikota) Number 13/2012 regarding on Guides for Information and Documentation Service Management Within Governmental Institution of Pematangsiantar as guidance procedures. This paper dis-cusses about the things that affect to implementation of this policy. Collecting data of this study is using field research. The finding of this study is there are eight things that affect to implemen-tation of PP No. 61/2010 on Pematangsiantar City Government. First, the standardize about policies and objectives; Second, the resources; Third, communication and strengthening the ac-tivities of the implementing agencies; Fourth, characteristics of the implementing agencies of public policy; Fifth, condition of social economic and political development; Sixth, the disposi-tion implementor or the attitude of the implementers of public policy; Seventh, the existence of the plan and the placement of the task correctly; Eight, Existence of compliance and the re-sponse implementing agencies.Keywords: Local government, regulation, public services.